Impact of Learning Discipline on Students' Qur'an Memorization Achievement - Syaiful Anam; Wahidmurni Wahidmurni; Mohammad Samsul Ulum; Widiyanto Widiyanto; Miftahul Ulum; Ahmad Barizi (STAI Hubbulwathan Duri, 2025)
This study examines the impact of learning discipline on the achievement of Qur'anic memorization among students in three Islamic boarding schools. Learning discipline is defined as students' consistent adherence to the rules governing the tahfidzul Qur'an process, particularly in terms of a serious attitude during Halaqoh sessions, attendance, and time management. A quantitative approach was employed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze the relationship between learning discipline and Qur'anic memorization achievement. Learning discipline was measured through three indicators: (X3.1) serious engagement in memorization during Halaqoh sessions, (X3.2) attendance, and (X3.3) time management. Data were collected from students enrolled in tahfidzul Qur'an programs at three Islamic boarding schools. The findings indicate that learning discipline has a significant positive effect on Qur'anic memorization achievement, as demonstrated by a P-value of 0.000 (0.005). This result confirms that students with higher levels of discipline perform better in memorization tasks. The study highlights the critical role of discipline in enhancing students’ memorization achievements. The results suggest that Islamic boarding schools should strengthen policies that encourage punctuality, attendance, and focused engagement in Halaqoh sessions to optimize students' tahfidz outcomes. The significant effect of learning discipline on Qur'anic memorization underscores its importance in tahfidzul Qur'an education. These findings provide valuable insights for educators and policymakers in improving the effectiveness of Qur'anic memorization programs in Islamic boarding schools.